Modern Targeted Strategies For The Treatment Of Colorectal Cancer With Metastatic Liver Lesions (The Peerian Journal, 2025)
The aim of the study was to assess the effectiveness of targeted therapy in the treatment of patients with colorectal cancer with liver metastases.